Introduction to Safe Space Training: Interactive Module for Promoting a Safe Space Learning Environment for LGBT Medical Students - Anthony Gacita; Emma Gargus; Toshiko Uchida; Patricia Garcia; Micheal Macken; Laura Seul; James Brucker; Diane B. Wayne (Association of American Medical Colleges, 2017)
Introduction Lesbian, gay, bisexual, and transgender (LGBT) students face challenges in achieving their educational goals. By understanding concepts surrounding sexual orientation and gender identity, faculty, staff, and students can support LGBT community members and provide a safe educational space. In order to address this we created a condensed training resource that focused on skill building and is easily implemented institution-wide for students, residents, fellows, faculty, and staff. Methods This module serves as an introduction to concepts integral to the LGBT community. It is structured into two sections and takes approximately 30 minutes to complete, including pre-/postevaluations. The first section of the module focuses on presenting basic information about the LGBT world experience and basic terminology. The second section contains two real-world scenarios aimed at demonstrating skills used to create a safe educational learning space. Each scenario contains interactive questions that allow participants to practice applying their new skills. Results To date, 89 institutional community members at the Northwestern University Feinberg School of Medicine have completed the module. Survey results demonstrate that the module was well-received and effective at improving attitudes towards creating a safe space. Discussion While this module provides a foundation in terminology and phenomena relevant to the LGBT experience, it is just one part of creating a positive institutional climate for LGBT community members. Additional in-person skills-based training should also be considered to complement and enhance this module's contents.